Coordinated expression of acetyl CoA synthetase and the ace operon enzymes in Escherichia coli in preparation for adaptation to acetate. Issue 9 (1st September 2022) - El-Mansi, Mansi; Afolabi, Olumide; Phue, Je-Nie; Shiloach, Joseph
Abstract : Successful adaptation of Escherichia coli to constant environmental challenges demands the operation of a wide range of regulatory control mechanisms, some of which are global, while others are specific. Here, we show that the ability of acetate-negative phenotype strains of E. coli devoid of acetate kinase (AK) and phosphotransacetylase (PTA) to assimilate acetate when challenged at the end of growth on acetogenic substrates is explicable by the co-expression of acetyl CoA-synthetase (AcCoA-S) and acetate permease (AP). Furthermore, mRNA transcript measurements for acs and aceA, together with the enzymatic activities of their corresponding enzymes, acetyl CoA synthetase (AcCoA-S) and isocitrate lyase (ICL), clearly demonstrate that the expression of the two enzymes is inextricably linked and triggered in response to growth rate threshold signal (0.4 h −1 ± 0.03: n4). Interestingly, further restriction of carbon supply to the level of starvation led to the repression of acs (AcCoA-S), ackA (AK) and pta (PTA). Further, we provide evidence that the reaction sequence catalysed by PTA, AK and AcCoA-S is not in operation at low growth rates and that the reaction catalysed by AcCoA-S is not merely an ATP-dissipating reaction but rather advantageous, as it elevates the available free energy (Δ G °) in central metabolism. Moreover, the transcriptomic data reinforce the view that the expression of PEP carboxykinase is essential in gluconeogenic phenotypes.